2015
DOI: 10.1517/17460441.2015.1032240
|View full text |Cite
|
Sign up to set email alerts
|

Positron-emission tomography molecular imaging of glia and myelin in drug discovery for multiple sclerosis

Abstract: Strengths of PET lie in the molecular selectivity, sensitivity and potential for absolute quantitation. Even now, translocator protein PET radioligands could be used in exploratory studies for interventions targeting brain microglial activation. The clinical and neuropathological meaningfulness of signal from PET radioligands reporting on astrocyte activation through cellular expression of either monoamine oxidase B or the I2-imidazoline receptor or metabolism of [(11)C]acetate can now explored. [(11)C] N-meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 79 publications
0
30
1
Order By: Relevance
“…We observed increased brain TSPO radioligand uptake in vivo in HIV-positive individuals on effective ART using [ 11 C]PBR28 PET, suggesting microglia (and, possibly, astroglial activation). 12 In contrast to some previous reports on TSPO radioligand uptake 9,11 in cognitively healthy PLWH, we found evidence for widespread increases in brain TSPO radioligand uptake. Regions of greatest TSPO uptake, and, by inference, greatest neuroinflammation, were found in subcortical brain gray matter, particularly in the basal ganglia (globus pallidus, caudate, and striatum).…”
Section: 10 All Observations)contrasting
confidence: 99%
See 1 more Smart Citation
“…We observed increased brain TSPO radioligand uptake in vivo in HIV-positive individuals on effective ART using [ 11 C]PBR28 PET, suggesting microglia (and, possibly, astroglial activation). 12 In contrast to some previous reports on TSPO radioligand uptake 9,11 in cognitively healthy PLWH, we found evidence for widespread increases in brain TSPO radioligand uptake. Regions of greatest TSPO uptake, and, by inference, greatest neuroinflammation, were found in subcortical brain gray matter, particularly in the basal ganglia (globus pallidus, caudate, and striatum).…”
Section: 10 All Observations)contrasting
confidence: 99%
“…12 [ 11 C]PBR28 is a second-generation TSPO radioligand with higher affinity for TSPO and a high displaceable binding fraction. 13,14 Unlike [ 11 C]PK11195, the affinity for the target protein is determined by the rs6971 single nucleotide polymorphism (SNP) in the TSPO gene, 15 and therefore incorporation of genotypic data enables an accurate quantitative interpretation of TSPO PET data.…”
mentioning
confidence: 99%
“…FRβ is not expressed in quiescent or resting microglia. As FRβ award macrophages to internalize molecules derived from folic acid, the development of tracers derived from folic acid could allowed the following of activated macrophages and microglia [162]. Moreover, in vitro studies showed that FRβ is specifically expressed by M2 polarized macrophages [163].…”
Section: Potential Alternative Molecular Targets For Activated Micmentioning
confidence: 99%
“…Myo-inositol is a glial cell marker, and its increase reflects glial cell (or astrocytic) activation and proliferation (Figure 1). 10,35,46 Different disease subtypes (e.g. PPMS and RRMS) show increased myo-inositol levels in the acute and chronic WM lesions of the brain and the spinal cord when compared to healthy controls.…”
Section: Myo-inositolmentioning
confidence: 99%
“…From a technical point of view, there are several limitations of MRS imaging, 11 which may hamper their use in the clinical setting and in clinical trials. 15 These include: 1) long acquisition times, more significantly for chemical-shift imaging (CSI) than for single-voxels MRS; 2) lower spatial resolution compared to MRI, 46 with minimal spatial information provided by single voxel MRS acquisition; 3) difficulties in differentiating between the intracellular and the extracellular pool of different metabolites and between GM and WM compartments within volumes of interest; 4) use of different scanners and acquisition protocols which can be responsible for incomplete agreement on metabolite concentrations; 5) spectra are influenced by variations in B0 and B1 magnetic fields, and there are pathology-related changes in the T1 and T2 relaxation times of the spectral metabolites that need to be considered when investigating patients. Furthermore, spinal cord MRS presents additional technical limitations, such as the small size of the cord, the susceptibility artefacts due to tissue-bone interfaces, and the motion artefacts arising from respiratory, arterial and cardiac activities, and systolic-related CSF and spinal cord pulsations.…”
Section: Limitationsmentioning
confidence: 99%